The Principle of Economic Justice in the Qur’an: A Legal Analysis of Shrinkage in Weights and Measures in Trade According to Qur’an 2:275 in Wahbah al-Zuhaili’s Tafsīr al-Munīr - Asep Sutarmin; Akh. Fauzi aseri; Anwar Hafidzi (Institut Agama Islam Persis Bandung, 2024)
In Tafsir al-Munir, Wahbah az-Zuhaili asserts that the principle of economic justice in Islam serves as a spiritual and social foundation that must color all mu’amalah (transactional) activities, wherein economic transactions should be based on the values of monotheism (tauhid), justice, prophethood, social responsibility, and an orientation toward the hereafter. Through his interpretation of QS. Al-Baqarah: 275, Wahbah highlights a firm prohibition against all forms of injustice, exploitation, and fraud in trade, particularly the practice of diminishing weights and measures. Natural shrinkage is still permissible as long as it is honestly disclosed to the buyer, while manipulative reduction intended to harm others is categorized as invalid (batil) and forbidden (haram). This study employs a qualitative-descriptive method based on library research, utilizing primary sources such as the Qur’an, hadith, and Wahbah az-Zuhaili’s tafsir, as well as secondary literature on Islamic economics. The findings indicate that Islamic economic justice demands transparency, honesty, and avoidance of unilateral exploitation, making legal regulation of weight reduction practices crucial for establishing a trading system that is not only legally valid but also ethical and meaningful according to sharia, in order to realize welfare and social justice in society